Two-sided manual machining method for three-axis CNC milling machine for small and medium-sized enterprises - Royke Vincentius Febriyana; Ramadhan S. Pernyata; Dita Andansari (National Research and Innovation Agency, 2022)
Small and medium-sized enterprises (SMEs) have a big role in Indonesian economic development. The government has set four strategies in an effort to boost Indonesian economic development. One of the four strategies mentions the SMEs, and the other mentions the use of 4.0 technology. Working capital has been the main issue need to be considered in the SMEs. Thus, the affordability must be considered in the use of 4.0 technology in SMEs. One of the 4.0 technologies that are possible to be used in the SMEs is a three-axis milling machine. One of the limitations of the machine is that it cannot do the back-side machining process. The paper examines the possibility of manual back-side machining on the three-axis milling machine without adding a rotary axis. Four methods were conducted by adding two-point markings on the x-axis, two-point markings on the y-axis, four-point markings on the x- and y-axis, and four-point markings on the x- and y-axis plus a series of offsetting processes. After conducting several qualitative observations and measurements on the mismatched position of the front and the back machining, and also analyzing the problems that emerged during the processes of the four different methods, it is concluded that adding four points markings on the x- and y-axis plus doing a series of offsetting processes is the best method to have two-sided manual machining with three-axis computer numerical control (CNC) milling machine.